2018
DOI: 10.1007/s13197-018-3366-9
|View full text |Cite
|
Sign up to set email alerts
|

Determination of free amino acids in tea by a novel method of reversed-phase high performance liquid chromatography applying 6-Aminoquinolyl-N-Hydroxysuccinimidyl carbamate reagent

Abstract: We describe a novel analytical method for quantification of free amino acids in tea using variable mobile phase pH, elution gradient and column temperature of reversed-phase high-performance liquid chromatography (RP-HPLC). The study of mobile phase pH 5.7 was chosen to simultaneous quantification of 19 free amino acids in tea, while it improved maximum resolution of glutamine, histidine and theanine. Elution gradient was adapted for enhancing the solution of free amino acids, mainly because of adjustment of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Free amino acids analysis. The determination of free amino acids in tea plant roots was performed as described 64,65 with minor modifications. Briefly, a HPLC system (Waters 2695) coupled to a fluorescence detector (Waters 2475) and an ultraviolet-visible detector (Waters 2489) was used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Free amino acids analysis. The determination of free amino acids in tea plant roots was performed as described 64,65 with minor modifications. Briefly, a HPLC system (Waters 2695) coupled to a fluorescence detector (Waters 2475) and an ultraviolet-visible detector (Waters 2489) was used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The results indicated that LOT contained higher water extract and total free amino acid concentrations and lower total tea polyphenol and crude fiber concentrations than LST for the same plucking. LST had fewer free amino acids, which may be related to the coarse leaves and stems (Li et al., 2018). These findings were consistent with our assumption.…”
Section: Resultsmentioning
confidence: 99%
“…The proposed method was further validated using a reported HPLC−UV quantification method for Ltheanine. 37 HPLC was performed on an Agilent 1100 Series system (Agilent Technologies, Inc., Pickerington, OH) equipped with an AccQ-Tag C18 amino acid analysis column (150 mm × 3.9 mm i.d. × 4-μm pore size, Waters Co. Ltd., Milford, MA) under the wavelength of 254 nm.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The derivatization was performed according to the method described by Li. 37 The mobile phase was isocratic and composed of 60% acetonitrile in ultrapure water with 10% AccQ-Tag Eluent A at pH 5.7 (Waters Co. Ltd., Milford, MA) to facilitate separation and detection of amino acids. The mobile phase flow rate was constant at 1.0 mL/min.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%